The Genetics of Postmating, Prezygotic Reproductive Isolation Between Drosophila virilis and D. americana - Sweigart, Andrea L. (Genetics Society of America, 2010)
Many studies have demonstrated the rapid diversification of reproductive genes that function after mating but before fertilization. This process might lead to the evolution of postmating, prezygotic barriers between species. Here, I investigate the phenotypic and genetic basis of postmating, prezygotic isolation between two closely related species of Drosophila, Drosophila virilis and D. americana. I show that a strong barrier to interspecific fertilization results in a 99% reduction in progeny production. A genetic interaction among maternal and paternal alleles at only a few loci prevents the fertilization of D. virilis females by D. americana males. These loci are autosomal and isolation acts recessively; the fertilization incompatibility is caused by at least two loci in the maternal D. virilis parent in combination with at least three loci in the paternal D. americana parent. These findings, together with results from classical experiments, suggest that male–female coevolution within D. americana may have driven postmating, prezygotic isolation between species.